The role of the transcription factor BRN2 in melanoma - Herbert, K (2018)
Expression of the POU-domain transcription factor BRN2 is crucial for the developing brain and drives proliferation and invasiveness in cancers of neural crest origin including melanoma. However, our understanding of BRN2 function and how its behaviour is modulated remains incomplete. We therefore aimed to investigate how protein:protein interaction and post-translational modification might influence the activity of BRN2 and how this impacts on melanoma cell phenotype. We show that, surprisingly, BRN2 binds DNA-damage response proteins rather than transcriptional co-factors and that following UVB irradiation, BRN2 rescues cells from apoptosis. Expression of apoptosis-induction genes in response to UVB is enhanced following knockdown of BRN2. Significantly BRN2 expression in tumours also correlates with an increased mutational burden. Mechanistically, BRN2 is rapidly recruited to DNA-damage sites in a PARP-dependent manner and requires DNA binding for efficient recruitment and rescue from apoptosis. Furthermore, post-translational modification of the transactivating domain of BRN2 by the UV-induced p38 stress kinase modifies the recruitment kinetics of BRN2 and its DNA binding ability, and p38 signalling disrupts a key BRN2 protein:protein interaction. Our findings identify a novel role for BRN2 in promotion of survival of melanoma cells in the face of genomic insult. These findings help us to understand the mechanisms that melanoma cells employ to tolerate high levels of genome instability with potential implications for neuronal development and tumours such as small cell lung cancer and neuroendocrine prostate cancer.